Elaboración de una guía metodológica de gerencia de proyectos en las áreas de integración, alcance, tiempo y costo para el montaje de plantas de concreto para Cemex Premezclados de Colombia (2015)
The main objective of this degree work is the development of a methodological guide for project management in the areas of integration, scope, time, cost and stakeholders (for this last area only the start process group is included) for the assembly of Cemex Premixture concrete plants in Colombia. Bearing in mind that during the specialization in Development and Integral Project Management for some of the subjects, the subject proposed for the degree work was used as a case study for some of the works, the gathering of information and background for these, as well as the results obtained were used for the preparation of the degree work, and specifically for the knowledge of the current state of the project management culture of the organization, which was based on the final workshop of the PMO subject and management maturity of projects. For the approach of the methodological guide, taking into account that the foundations indicated in the Guide of the PMBOK - Fifth Edition were followed, it was sought to have correspondence between areas of knowledge and groups of processes for the management of projects, applied to the structure of work that is currently managed in the area of ​​projects of the Vice Presidency of Solutions for Builders, so that the proposed guide can be implemented in practice and thus be useful for the organization. For the above, the development proposed in the PMBOK Guide - Fifth Edition for each of the selected procedures was reviewed, the respective procedure was elaborated with its objective, scope, flowchart, description and required formats. Likewise, a general review of all the procedures was carried out to validate the integrality and coherence of these, which in turn served to consolidate the approach of the process map for the management of the organization's projects. Finally, the procedures and formats were applied to a practical case, "Puente Aranda L2 concrete plant assembly", which allowed the optimization of the procedures and formats proposed and elaborated initially, besides validating the practicality in its use and its completeness as soon as what is required as inputs and outputs. The 24 selected procedures are presented in 19 documents, taking into account that during their preparation the possibility and practicality of integrating some of them was identified. Likewise, 24 formats were prepared for the registration of the implementation of each of the procedures, as well as a process map that allows to have an initial guide to the sequence in which they can be applied. With the above, we intend to initiate the formalization and strengthening of the project management culture in the organization, since according to the reviewed background this is informal and does not cover the main areas of knowledge and process group of the PMBOK Guide - Fifth edition.